Lack Of Association Between IL-6 Gene Polymorphisms And Rheumatoid Arthritis In Turkish Population - Çoker, Ajda; Arman, Ahmet; Sarıöz, Özlem; İnanç, Nevsun; Direskeneli, Rafi Haner (Springer Heidelberg, Tiergartenstrasse 17, D-69121 Heidelberg, Germany, 2012)
Inflammatory cytokines play an important role in the pathogenesis of rheumatoid arthritis (RA). One of candidate genes is interleukin-6 (IL-6), and single-nucleotide polymorphisms in the promoter region of IL-6 were found to be associated with RA. The aim of this study was to determine the association between IL-6 promoter polymorphisms (-174, -572, -597) and RA in Turkish population. A total of 425 subjects were recruited into the study (247 healthy controls and 178 RA). The promoter region of IL-6 gene was amplified by PCR using DNAs from patients and the controls, and their PCR products were digested by suitable enzymes. No significant association was found between RA and -174 genotype distribution (P = 0.535) and allele frequency (P = 0.230). There was also no relationship between -572 (P = 0.150) and -597 (P = 0.912) gene polymorphism and RA. Our results suggested that IL-6 gene promoter polymorphisms have no association with RA in Turkish population.
Keywords: IL-6; polymorphisms; rheumatoid arthritis; interleukin-6 receptor; cytokine; genotypes; disease; damage; polimorfizmler; romatizmal artrit; interlökin-6 reseptörü; sitokin; genotipler; hastalık; hasar